The identification of potato genotype diversity based on morpho-agronomy and nutritional traits in the highland areas of Papua, Indonesia - SARASWATI PRABAWARDANI; DARMA J. YOGI; NOUKE L. MAWIKERE; NI MADE GARI; ALCE I. NOYA; SARTJI TABERIMA; IRNANDA AF DJUUNA; FIONA D. N. LUHULIMA (Society for Indonesian Biodiversity, 2023)
Abstract. Prabawardani S, Yogi DJ, Mawikere NL, Gari NM, Noya AI, Taberima S, Djuuna IA, Luhulima FDN. 2023. The identification of potato genotype diversity based on morpho-agronomy and nutritional traits in the highland areas of Papua, Indonesia. Biodiversitas 24: 5137-5145. Potatoes (Solanum tuberosum L.) are a potential food crop in terms of economic value and food security, and, therefore, its development must be considered. The missionaries introduced several potato genotypes from 1959 to the 1960s in Papua; however, this area has not been widely studied. This research aimed to identify the agro-morphological characteristics and analyze the tuber nutritional traits of potato genotypes. The research was conducted in Mimin Village, Oksop Sub-district, Pegunungan Bintang District of Papua Province, Hungku Village, Anggi Sub-district, Pegunungan Arfak District of West Papua Province. The research in both locations was designed using a descriptive method, and the samples were collected based on the random sampling technique. There were 2 potato genotypes found in Mimin (KM-O and KP-O) and 5 in Hungku (KM-A, KH-A, KP-A, KB-A, and KT-A) with quite diverse traits, particularly in tuber components. With several prominent morphological characters, potato genotypes from Hungku (KM-A, KBH-A, KT-A) produced the highest yields (0.8 kg/plant). Based on the agro-morphological and nutritional characteristics, it shows the formation of two main clusters with a dissimilarity index of Squared Euclidean Distance ranging from 6.112 to 46,643. Cluster one consisted of genotypes KM-O, KP-O, KM-A, and KH-A, and cluster two consisted of KP-A, KBH-A, and KT-A genotypes, and the dissimilarity mainly lies in the yield and nutrient characters. Based on the nutrient analysis, the highest dry matter content was found in KH-A. The highest starch content was in KP-O and KBH-A, and the highest reducing sugar was in KM-A. The potato genotype with the lowest reducing sugar content was KP-A. Each potato genotype shows various agro-morphological and nutritional characteristics that can be used as a basis material for plant breeding.